Monitoring the treatment with medical cannabis in patients with chronic pain due to severe osteoarthritis through the analysis of THC, CBD, and metabolites in hair - Basile, Giuseppe; Tronconi, Livio; Basile , Michela; Bolcato, Vittorio (Acta Biomedica Atenei Parmensis, 2024)
Cannabis-based pharmaceutical preparations, or medical cannabis, are an emerging and valid option for the treatment of drug-resistant chronic pain associated with severe osteoarthritis. This article reviews the clinical implications and future developments in the therapeutic management of patients with resistant chronic pain due to severe osteoarthritis treated with medical cannabis. The use of medical cannabis may better manage resistant chronic pain due to osteoarthritis compared to the side effects associated with long-term anti-inflammatory drugs or the high risk of dependence with opioids. Different combinations of tetrahydrocannabinol (THC) and cannabidiol (CBD) can be tailored to the specific needs of the patient, optimising therapeutic efficacy and minimising side effects. The hair matrix allows for easier, non-invasive and long-term monitoring, with the possibility of simultaneous and accurate quantification of THC, CBD and their major metabolites. Hair matrix drugs monitoring could improve both the efficacy and safety of treatment, reducing the risk of unwanted side effects or improper assumption. In the future, further developments could include the ability to distinguish between different varieties of cannabis preparations and to detect an even wider range of metabolites, providing an even more comprehensive picture of therapeutic cannabis use.